Research on Lateral Force of Pile Based on Liquefaction Site Effect - Zuo Xi; Zhou Enquan (Shock and Vibration)
This paper presents a theoretical investigation on the lateral force of pile in liquefaction site. Regarded liquefied soil as fluid, the vector method can be used to analyze the liquefaction velocity field and solve the analytical solution of the dynamic field by making use of the principle of fluid mechanics. In addition, by solving the velocity field with vector symbol operation method, the analytical expression of the lateral force in the liquefied flow field is obtained, and the sensitivity of the parameters in the analytical expression is analyzed. The results show that the stress field of the pile contains both the pressure resistance caused by surface pressure and the friction resistance caused by shear stress, when the liquefied soil flows laterally. The lateral forces on the pile are mainly composed of inertial forces and damping forces and are related to density, fluid viscosity, pile radius, and vibration frequency. With the increase of density, fluid viscosity, and pile radius, the added mass and added damping increase gradually. In a certain range, added mass and added damping are sensitive to vibration frequency.